Characterization of caffeine crystals obtained from the extraction process of green robusta coffee beans - Tri Hariyadi; Ayu Ratna Permanasari; Iwan Ridwan; Bambang Soeswanto; Teguh Taufiqurohim; Unung Leoanggraini; Fania Hidayati; Renata Naomi Cinta Sedjati; Mentik Hulupi (Jurnal Rekayasa Proses, 2026)
Robusta coffee contains a higher caffeine content, ranging from 1.6–2.4%, nearly twice as much as Arabica coffee, which contains only 0.9–1.2%. Caffeine content is widely utilized in various fields, such as pharmaceuticals and the food and beverage industry. This study aims to analyze the effect of temperature and time on the solid–liquid extraction process of green coffee beans, as well as to evaluate the effectiveness of two different solvents in the liquid–liquid extraction process for obtaining caffeine crystals. Solid–liquid extraction was carried out at temperature variations of 70°C, 80°C, 90°C, and 97°C, with durations of 30 minutes, 45 minutes, 60 minutes, 75 minutes, and 90 minutes. Liquid–liquid extraction was performed using two types of organic solvents, namely chloroform and dichloromethane. The results were analyzed by measuring caffeine purity using a melting point apparatus and high-performance liquid chromatography (HPLC) based on retention time parameters, as well as determining caffeine concentration using a UV–Vis spectrophotometer. The optimum temperature and time for solid–liquid extraction were found to be 97°C for 60 minutes. Liquid–liquid extraction yielded a caffeine content of 2.18 mg/g using chloroform, and 1.38 mg/g using dichloromethane. Based on melting point and HPLC retention time testing, the caffeine crystals obtained from liquid–liquid extraction with dichloromethane showed higher purity, with a melting point of 236°C and a retention time of 2.06 minutes. These values are close to those of pure caffeine, which has a melting point of 236°C and a retention time of 2.01 minutes, compared to the caffeine crystals obtained using chloroform.